Public knowledge, attitudes, practices, and barriers to skin cancer screening in the United Arab Emirates - Anan S. Jarab; Walid Al-Qerem; Karem H. Alzoubi; Mariam Al Mohammad; Shrouq R. Abu Heshmeh; Yazid N. Al Hamarneh; Tareq Mukattash; Maher Khdour (PLoS ONE, 2025)
Objective To assess knowledge, attitude, practice, and barriers to skin cancer screening among the general population of the United Arab Emirates (UAE). Methods In this cross-sectional study, an online-based questionnaire was distributed via online social media sites such as Facebook, WhatsApp, Twitter, and others to the residents of the UAE. The questionnaire evaluated socio-demographics, knowledge (8 items), attitudes (10 items), practices (14 items), and barriers (9 items) in the context of skin cancer screening. A binary logistic regression was conducted to assess variables associated with practice levels. Results The study included 924 participants (51.9% females), with a median (IQR) age of 32 (22–44) years. Results showed a window for knowledge improvement [median = 4 (3–6) out of a maximum potential score of 8], unfavourable attitudes [median = 37 (33–39) out of a maximum potential score of 50], inadequate practices [median = 41 (31–45) out of a maximum possible score of 70]. The most common barriers to skin cancer screening were lack of knowledge about skin cancer (74.1%), lack of awareness of the need for skin cancer screening (72.2%), and absence of symptoms (54.1%). Older age (OR = 0.985, 95%CI: 0.971–0.998) and lack of health insurance (OR = 0.478, 95%CI: 0.301–0.758) were associated with lower screening practices. Female gender (OR = 1.833, 95%CI: 1.361–2.469), being married (OR = 1.415, 95%CI: 1.006–1.992), being a non-smoker (OR = 1.568, 95%CI: 1.045–2.352) or a former smoker (OR = 2.555, 95% CI: 1.082–6.034), and more favourable attitudes (OR = 1.071, 95%CI: 1.044–1.096) were associated with higher screening practices. Conclusion The UAE population exhibited moderate knowledge, unfavourable attitudes, and inadequate practices regarding skin cancer screening, with several barriers identified. Targeted online and in-person awareness campaigns are crucial for improving public understanding and attitudes, thereby enhancing screening practices, especially among older adults, males, smokers, and those without health insurance.